Transport and kinetics at carbon nanotube- redox enzyme composite modified electrode biosensors. Part 2. Redox enzyme dispersed in nanotube mesh of finite thickness. - LYONS, MICHAEL EDWARD (Electrochemical Science Group, 2009)
A mathematical model describing the transport and kinetics of substrate and redox mediator in surface deposited films of finite thickness is described. These bio-catalytically active chemically modified electrodes comprise redox enzymes immobilized in a highly dispersed mesh of single walled carbon nanotubes (SWNT) which are in turn immobilized on a support metal surface. A small molecule redox mediator is used to both regenerate the reduced enzyme and to transfer electrons either to the carbon nanotube surface or to the underlying support electrode surface thereby generating a current which can be measured. The pertinent transport and kinetic differential equations of both substrate and redox mediator are formulated along with suitable boundary conditions and are solved analytically to derive suitable approximate analytical expressions for the current response expected for the system under steady state batch amperometric conditions. The kinetics of substrate and mediator within the nanotube layer are summarized in terms of a kinetic case diagram.
PUBLISHED
Keywords: Amperometric enzyme biosensor modeling; SWNT modified electrodes; enzyme bioelectrocatalysis ; immobilized redox enzyme systems